Dissection of a replication origin of Xenopus DNA. - Chambers, J C (1982)
A previously cloned 503-base pair (bp) EcoRI segment of genomic DNA from Xenopus laevis selected for enhancement of replication of its vector plasmid was moved to the EcoRI site of pBR322. This plasmid designated pJCC31 and five other clones, which were made by cleaving the 503-bp segment in relation to a dispersed repeated sequence and subcloning, were compared with pBR322 for replication by microinjection into Xenopus eggs. The replication measured by incorporation of a 32P-labeled nucleotide as well as semiconservative segregation and dilution of N6-methyladenine at the EcoRI sites showed pJCC31 to be about 15 times as efficient as pBR322. The next most efficient subclone, pJCC31-2, contains an insert with a complete 320-bp dispersed repeated sequence bracketed by an 8-bp direct repeat. This observation, along with our previous report that repeated sequences of the Alu family in the human genome enhanced replication of the vector plasmid nearly as much as that of the presumptive Xenopus origin, leads to the hypothesis that members of a subset of the short dispersed repeated sequences in vertebrates function as origins for chromosomal replication. Preliminary studies also show that the presumptive Xenopus origin contains a RNA polymerase promoter that increases the transcription of the plasmid when it is microinjected into Xenopus oocytes.